Evaluation of determinants of food waste in family households in the greater porto area based on self- reported consumption practices - Portugal, T (2020)
Despite food waste occurring along the entire food supply chain, a significant proportion occurs in domestic settings. Large quantities of domestic food waste have been attributable to consumer behaviors during buying, cooking, consumption, and disposal. The main objective of this research was to understand the major determinants of household food waste from families in the north of Portugal. A convenience sample was used, which was drawn from households in the Greater Porto Area. Data were collected through a self-reported questionnaire that included three groups of structured questions related to perceived behavior and attitudes towards food consumption, leftover usage, and food waste. Exploratory data analysis was used to identify underlying dimensions. No relationships were found between socio-demographic data and food waste, buying behavior, or destination/use of leftovers. The majority of the participants reported a high level of planning of their grocery shopping. Fruits and vegetables presented the highest frequency of consumption, followed by sources of carbohydrates and sources of proteins. The storage of cooked food from different food groups presented a single factor, grouping the majority of the individual food leftovers, going from fruits and vegetables to sources of carbohydrates and proteins. The reported levels of wastage of the different food products were grouped into three dimensions: waste of vegetables, waste of protein sources, and waste of sources of carbohydrates. Waste of precooked foods emerged as an independent item, and it was the individual item with the highest frequency. The families studied reported a positive attitude concerning buying, consumption, and wastage, revealing a particular awareness of food waste and its social and environmental impact. (c) 2020 by the authors.